Kolaborasi Pengawasan Penggunaan Tenaga Kerja Asing di Sumatera Barat (Studi Kasus: Tenaga Kerja Asing di Kabupaten Pasaman Barat) - Cindy Putri Khumairoh; Lince Magriasti (YASIN, 2026)
The supervision of the use of foreign workers (TKA) is an important instrument to ensure compliance with labor and immigration regulations. This issue emerged when 13 foreign workers from China were found allegedly working illegally at PT Gamindra Mitra Kusuma (GMK), West Pasaman Regency, thereby indicating that weaknesses remain in supervision, particularly in interagency coordination. This study aims to analyze collaborative supervision of the use of foreign workers in West Sumatra, identify challenges in supervising illegal foreign workers, and describe the efforts made to address these problems. This study used a qualitative method with a descriptive approach. Data were obtained through interviews, documentation, and literature study, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that collaborative supervision of foreign workers in West Sumatra has been implemented through the Foreign Nationals Monitoring Team (TIMPORA), involving the Manpower and Transmigration Office of West Sumatra Province, the Regional Technical Implementation Unit for Labor Supervision Region II, the Agam Class I Non-TPI Immigration Office, and other relevant agencies. This collaboration is realized through coordination, information exchange, document examination, field supervision, and joint operations in accordance with the duties and authority of each agency. Based on Sondang P. Siagian’s theory of the supervision process, the stages of establishing work standards, measuring work results, and taking corrective action have been implemented, but the effectiveness of supervision has not been optimal because there are still differences in perspectives between labor and immigration supervision, miscommunication within TIMPORA, a limited number of supervisors, the broad scope of the supervision area, limited budget and operational facilities, and a lack of corporate transparency in reporting the use of foreign workers. The efforts undertaken include strengthening field supervision, providing guidance and socialization to companies, reinforcing coordination through TIMPORA, implementing integrated supervision, and optimizing the Aplikasi Pengawasan Orang Asing (APOA). The conclusion of this study affirms that the effectiveness of foreign worker supervision in West Sumatra is highly dependent on cross-agency collaboration that is coordinated, integrated, and supported by an adequate supervision information system. The implications of this study provide practical contributions to strengthening the governance of foreign worker supervision and preventing violations related to the illegal use of foreign workers at the regional level.